Ecological urbanism - Mostafavi, Mohsen; Doherty, Gareth (Lars Muller Publishers, 2016)
"While climate change, sustainable architecture and green technologies have become increasingly topical issues, concerns regarding the sustainability of the city are rarely addressed. The premise of Ecological Urbanism is that an ecological approach is urgently needed both as a remedial device for the contemporary city and an organizing principle for new cities. Ecological Urbanism, now in an updated edition with over forty new projects, considers the city using multiple instruments and with a worldview that is fluid in scale and disciplinary focus. Design provides the synthetic key to connecting ecology with an urbanism that is not in contradiction with its environment. The book brings together practitioners, theorists, economists, engineers, artists, policymakers, scientists and public health specialists, with the goal of providing a multilayered, diverse and nuanced understanding of ecological urbanism and how it might evolve in the future. The promise is nothing short of a new ethics and aesthetics of the urban"--Provided by publisher.